Perancangan Alat Monitoring Arus Bocor pada Kabel 20 kV Menggunakan Filter Kalman Berbasis Internet of Things - Sitanggang, Adi Franata H; Prabowo, Yuliyanto Agung (Elektrika, 2022)
One of the problems that often occurs in the use of ground cables is insulation failure. This condition can cause leakage current in the 20 kV cable on the secondary side of the transformer. The greater the value of the leakage current, the more heat will cause the insulation to worsen. If this condition is not handled immediately, it can lead to the opportunity for a short-circuit current between the phase and ground. Therefore, an Internet of Thing-based monitoring tool is needed that can determine the amount of leakage current contained in the 20 kV cable on the secondary side of the transformer by applying the Kalman filter method and sending it to the substation operator using Wifi. Based on the test, it was found that the implementation of this monitoring tool obtained more constant measurement results than the actual measurement value using a measuring instrument with an average error per phase, 1.5594% phase R, 1.5535% phase S, 1.5548% phase T.